Analisis Pengaruh Produk Domestik Regional Bruto, Jumlah Penduduk, Nilai Tukar, dan Suku Bunga terhadap Penerimaan Pajak di Provinsi Sumatera Utara - Nazlia Wibowo (Jurnal Studi Akuntansi Pajak Keuangan, 2025)
This study aims to determine and analyze the influence of Gross Regional Domestic Product (GRDP), population, exchange rates, and interest rates on tax revenue in North Sumatra Province. This study uses secondary data with a panel data type, namely a combination of time series and cross-sectional data. The time series data covers the period 2015 to 2020, while the cross-sectional data covers 11 working areas of the Directorate General of Taxes in North Sumatra Province. Using EViews 11 software, the results show that simultaneously, GRDP, population, exchange rates, and interest rates influence tax revenue in North Sumatra Province. Partially, GRDP has a positive and significant effect, population has a positive but insignificant effect, exchange rates have a negative and significant effect, and interest rates have a positive but insignificant effect on tax revenue in North Sumatra Province.